CAT KUKU SEBAGAI GAYA HIDUP DAN IDENTITAS SOSIAL PEREMPUAN DI HINDIA BELANDA TAHUN 1920-1942 - Salsabila, Atika; Skober, Tanti Restiasih (Metahumaniora, 2026)
This study is titled “Nail Polish as a Symbol of Women’s Social Lifestyle in the Dutch East Indies, 1920–1942.” It aims to explain the development of nail polish usage and the social meanings attached to this aesthetic practice within colonial society in the Dutch East Indies. The focus of the study is directed at how nail polish evolved from a mere body care practice into a symbol of modernity, social status, and women’s identity within the colonial social structure. This research employs a socio-cultural historical approach by applying Pierre Bourdieu’s Theory of Social Distinction to analyze how cosmetic consumption practices function as markers of social class. The method used is the historical method, which consists of four stages: heuristics (source collection), verification (internal and external source criticism), interpretation, and historiography. The research sources include cosmetic advertisements, articles from colonial women’s magazines, Dutch-language newspapers, and visual documentation from colonial archives.The findings indicate that the use of nail polish in the Dutch East Indies developed gradually. In the early 20th century, nail care was primarily understood as part of women’s hygiene and bodily neatness. Entering the 1920s, the emergence of imported products such as Cutex marked the introduction of nail polish as a modern beauty commodity associated with Western lifestyles. In the 1930s, the use of nail polish became increasingly popular through advertisements, print media, and colonial consumption spaces, eventually becoming a symbol of urban women’s modernity.However, access to these products was not evenly distributed. Elite European, Indo-European, and educated indigenous women had greater access to imported cosmetics, while middle- and lower-class women adapted nail aesthetic practices using local materials such as henna leaves. This study concludes that nail polish functioned not only as a cosmetic product but also as a reflection of the dynamics of modernity, social class stratification, and the negotiation of women’s identities in the Dutch East Indies during the period 1920–1942.